OP0245 PRESERVATION OF LUNG FUNCTION OBSERVED IN A PHASE 3 RANDOMIZED CONTROLLED TRIAL OF TOCILIZUMAB FOR THE TREATMENT OF EARLY SSC. (June 2019) - Khanna, Dinesh; Lin, Celia J. F.; Goldin, Jonathan; Kim, Grace; Kuwana, Masataka; Allanore, Yannick; Batalov, Anastas; Butrimiene, Irena; Carreira, Patricia; Matucci-Cerinic, Marco; Distler, Oliver; Kaliterna, Dušanka Martinović; et al.
Abstract : Background: The anti–IL6 receptor-α antibody tocilizumab (TCZ) demonstrated numerical improvement in modified Rodnan skin score (mRSS) and clinically relevant preservation of lung function (LF) (assessed by forced vital capacity [FVC]) in systemic sclerosis (SSc) patients (pts) in a ph 2 trial. 1 Objectives: Report the efficacy and safety (sft) of TCZ vs placebo (PBO) in SSc pts from the double-blind period of ph 3 trial (NCT02453256 ). Methods: SSc pts were randomly assigned 1:1 to weekly subcutaneous TCZ 162 mg or PBO for 48 wks. Primary endpoint was mean difference (diff) in change (Δ) from baseline (BL) to wk 48 in mRSS for TCZ vs PBO. Key secondary endpoints were ΔBL%-predicted FVC (ppFVC) and time to Tx failure (time from first study treatment (Tx) to first occurrence of death, decline in FVC >10%, increase in mRSS >20% and mRSS ≥5, or occurrence of predefined SSc-related Cx). Chest high-resolution computed tomography (HRCT) and ACR Combined Response in SSc (CRISS) were exploratory endpoints. Results: Of 106 PBO- and 104 TCZ-treated pts, 81% were women and 31% had previous or concurrent interstitial lung disease based on history. BL mean values were age 48 yrs, SSc duration 23 mts, mRSS 20.4, ppFVC 82.1%, and ppDLCO 75.6%. Mean BL computer-assisted quantitative lung fibrosis of the most affected lobe (QLF-LM) was 4.7% for the PBO group and 5.5% for the TCZ group. At wk 48, the primary endpoint was not significant (ΔBL mRSS: PBO, −4.4; TCZ, −6.1; adjusted least squares mean diff, −1.7 [95% CI: −3.8, 0.3]; p =0.098) (Fig 1A). All p values for other endpoints were nominal. The cumulative distribution of wk 48 ΔBL ppFVC favored TCZ over PBO (median [IQR]: PBO, −3.9 [−7.2, 0.6] vs TCZ, −0.6 [−5.3, 3.9]; van Elteren nominal p =0.0015). The diff in mean ΔBL FVC at wk 48 between Tx groups was 167 mL (95% CI: 83, 250), favoring TCZ (Fig 1B). At wk 48, 5 (5.4%) TCZ-treated pts experienced ≥10% absolute decline in ppFVC compared with 15 (16.5%) for PBO. The HR (95% CI) for time to Tx failure was 0.6 (0.4, 1.1), numerically favoring TCZ (Cox proportional hazards model; p =0.082). ACR CRISS scores favored TCZ over PBO at wk 48: median (IQR), 0.89 (0.09-1.00) vs 0.25 (0.00-0.99) ( p =0.023). HRCT showed less progression of lung fibrosis for TCZ than for PBO, which supports the FVC results. Sft results were consistent with Cx of SSc and the established TCZ sft profile; SAEs were reported by 17% of PBO pts and 13% of TCZ pts; serious infections were reported by 7% and 2% of pts, respectively. Conclusion: The primary mRSS endpoint was not met; however, TCZ Tx resulted in clinically relevant differences in FVC with preservation of LFS and improvement in fibrosis, measured by HRCT, in SSc pts. Disclosure of Interests: : Dinesh Khanna Shareholder of: Eicos Sciences, Inc, Grant/research support from: Bayer, BMS, Pfizer, Horizon, Consultant for: Actelion Acceleron, Arena, Bayer, BI, BMS, CSL Behring, Corbus, Cytori, GSK, Genentech/Roche, Galapagos, Employee of: Elcos Sciences, Inc, Celia J. F. Lin Shareholder of: Genentech, Employee of: Genentech, Jonathan Goldin: None declared, Grace Kim Grant/research support from: GenenTech, NHLBI, Consultant for: MedQIA LLC, Masataka Kuwana Grant/research support from: Actelion, Consultant for: Chugai, Reata, GlaxoSmithKline, Bayer, Boehringer-Ingelheim, Corpus, CSL-Berling, Mochida, Speakers bureau: Actelion, Pfizer, Bayer, Nippon Shinyaku, Chugai, Yannick Allanore Grant/research support from: Inventiva, F Hoffman La-Roche, Sanofi, BMS, Pfizer, Consultant for: Actelion, Bayer, BMS, Boehringer, Roche, Sanofi, Anastas Batalov: None declared, Irena Butrimiene: None declared, Patricia Carreira: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: Actelion, BMS; MSD, Janssen, Oliver Distler Grant/research support from: Prof. Distler received research funding from Actelion, Bayer, Boehringer Ingelheim and Mitsubishi Tanabe to investigate potential treatments of scleroderma and its complications, Consultant for: Prof. Distler has/had consultancy relationship within the last 3 years with Actelion, AnaMar, Bayer, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, iQvia, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Serodapharm and UCB in the area of potential treatments of scleroderma and its complications. In addition, he had/has consultancy relationship within the last 3 years with A. Menarini, Amgen, Abbvie, GSK, Mepha, MSD, Pfizer and UCB in the field of arthritides and related disorders, Dušanka Martinović Kaliterna: None declared, Carina Mihai Consultant for: Received consulting fees or other remuneration from Actelion, Geneva, Roche, and Rofarm, Consultant for: F. Hoffmann-La Roche, Actelion, Geneva Romfarm, Mette Mogensen: None declared, Marzena Olesińska Consultant for: F. Hoffmann-La Roche, Janet Pope Consultant for: Eli Lilly and Company, Gabriela Riemekasten Consultant for: Chugai, F. Hoffmann-La Roche, Speakers bureau: Chugai, F. Hoffmann-La Roche, Tatiana Sofía Rodriguez-Reyne Grant/research support from: F. Hoffmann-La Roche, Maria Jose Santos: None declared, Jacob M. van Laar Grant/research support from: Genentech, Consultant for: F. Hoffmann-La Roche, Helen Spotswood Shareholder of: Roche Products Ltd., Employee of: Roche Products Ltd., Jeffrey Siegel Shareholder of: Genentech, Consultant for: Genentech, Angelika Jahreis Shareholder of: F. Hoffmann-La Roche, Employee of: Genentech, Daniel Furst Grant/research support from: F. Hoffmann-La Roche, Genentech, Christopher Denton Grant/research support from: GlaxoSmithKline, Inventiva, CSF Behring, Consultant for: Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Bayer